Using Bionics to Restore Sensation to Reconstructed Breasts - Lindau, Stacy T.; Bensmaia, Sliman J. (Frontiers in Neurorobotics, 2020)
Mastectomy often leads to a complete desensitization of the chest, which in turn can give rise to diminished sexual function and to disembodiment of the breasts. One approach to mitigate the sensory consequences of mastectomy is to leverage technology that has been developed for the restoration of sensation in bionic hands. Specifically, sensors embedded under the skin of the nipple-areolar complex can be used to detect touches. The output of the sensors then drives electrical stimulation of the residual intercostal nerves, delivered through chronically implanted electrode arrays, thereby eliciting tactile sensations experienced on the nipple–areolar complex. The hope is that the bionic breast will restore a woman’s sense that her breast belongs to her body so she can experience the pleasure of an embrace and derive the benefit of the sensual touch of her partner.